A Warm Touch in a Cold Cell: Inmates' Views on Conjugal Visits in a Maximum-Security Women's Prison in Israel. (December 2013) - Einat, Tomer; Rabinovitz, Sharon
Conjugal visits are believed to have positive effects during and after confinement. Yet, studies on the dynamics of such visits from women's point of view and their attitudes toward such visits are sparse. This study sought to identify and analyze female inmates' attitudes toward conjugal visits, describe the dynamics of conjugal visitations, and examine the meaning of conjugal visitation programs to the participants. The findings of this study reveal that (a) female inmates perceive conjugal visits as a significant and positive program in the prison, (b) these visits ease their pains of imprisonment and help to strengthen their relationships with their partners, and (c) nevertheless, the inmates express some criticism toward the poor condition of the visitation facilities and their unsatisfactory upkeep, claiming that such conditions limit their ability to feel and act freely during the meetings.